Königtum und Gottesherrschaft Untersuchungen zur alttestamentlichen Monarchiekritik - Müller, Reinhard (Mohr Siebeck, 2004)
Kingship and Gods Reign. Studies of the Criticism of the Monarchy in the Old Testament.
PublicationDate: 20200518
Keywords: Altes Testament -- Königstum -- Gottesherrschaft -- Monarchie -- Old Testament